2018
DOI: 10.1016/j.jphs.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effect and mechanism of Kursi Wufarikun Ziyabit in L6 rat skeletal muscle cells

Abstract: Kursi Wufarikun Ziyabit (KWZ) is a traditional prescription that used in folk tea drinking for its health care effect in treatment of type 2 diabetes mellitus (T2DM) in central Asia. However, the underlying mechanism of KWZ in T2DM has not been investigated extensively. This study designed to observe the effect of KWZ on glucose consumption and assess the molecular mechanism on associated proteins in insulin signaling and ER stress pathway in L6 rat skeletal muscle cells. The results showed that, KWZ exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Similar to the findings in hepatocytes and liver tissue described above, various tea constituents such as EGCG, black tea polyphenols, GRE, pure aspalathin, Pu-erh tea, and Kursi Wufarikun Ziyabit extract also enhanced PI3K/AKT signaling, GLUT4 content and translocation, and glucose uptake in cultured L6 myotubes, C2C12 mouse skeletal muscle cells, and isolated muscle tissue. 56,71,[73][74][75]79 Of note, Kamakura et al 75 compared the effects of a green Rooibos extract (GRE) (containing 6.6% aspalathin as the major flavanoid) with that of pure aspalathin and identified differential effects on AKT activation and glucose transport in L6 myotubes, demonstrating that the biological effects of individual tea constituents may differ from those of the complex extracts from which they were derived. In in vivo animal studies, PI3K activation and increased GLUT4 translocation induced by EGCG, Fu Brick tea, and Labrador tea in muscle tissue were associated with improved whole-body glucose tolerance.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the findings in hepatocytes and liver tissue described above, various tea constituents such as EGCG, black tea polyphenols, GRE, pure aspalathin, Pu-erh tea, and Kursi Wufarikun Ziyabit extract also enhanced PI3K/AKT signaling, GLUT4 content and translocation, and glucose uptake in cultured L6 myotubes, C2C12 mouse skeletal muscle cells, and isolated muscle tissue. 56,71,[73][74][75]79 Of note, Kamakura et al 75 compared the effects of a green Rooibos extract (GRE) (containing 6.6% aspalathin as the major flavanoid) with that of pure aspalathin and identified differential effects on AKT activation and glucose transport in L6 myotubes, demonstrating that the biological effects of individual tea constituents may differ from those of the complex extracts from which they were derived. In in vivo animal studies, PI3K activation and increased GLUT4 translocation induced by EGCG, Fu Brick tea, and Labrador tea in muscle tissue were associated with improved whole-body glucose tolerance.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Against this background, several studies have demonstrated that tea constituents could improve glucose metabolism in animal and cell culture models by enhancing insulin signaling through the IRS/PI3K/AKT pathway in the liver and muscle, and by regulating the content and activity of glucose transporters in these tissues (Table ). …”
Section: Resultsmentioning
confidence: 99%
“…Glucose uptake study can be performed by different experimental in-vitro methods skeletal muscle cell line, isolated diaphragm and isolated rat jejunum. 38,39 The glucose uptake study was performed using isolated rat jejunum and rat hemidiaphragm. 40,41 The result revealed fruit extract of Ficus Lacor Buch.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we optimized the best proportion and extraction conditions, identified the main components, and detected the antidiabetic activities by protein tyrosine phosphatase-1B (PTP-1B) and α -glucosidase inhibitors [ 21 ]. Then, the hypoglycemic effect of KWZ on L6 rat skeletal muscle cells and its mechanism was investigated, mainly including the glucose consumption, treatment time, and the expression of the major proteins in insulin resistance and ER stress signaling pathways [ 22 ]. However, the molecular mechanisms of KWZ are still unknown on db/db T2DM mice.…”
Section: Introductionmentioning
confidence: 99%
“…en, the hypoglycemic effect of KWZ on L6 rat skeletal muscle cells and its mechanism was investigated, mainly including the glucose consumption, treatment time, and the expression of the major proteins in insulin resistance and ER stress signaling pathways [22]. However, the molecular mechanisms of KWZ are still unknown on db/db T2DM mice.…”
Section: Introductionmentioning
confidence: 99%